Completeness of the Hospital Cancer Registry at a hospital in Florianópolis - Luz, Clarissa Medeiros da; Deitos, Julia; Siqueira, Thais Cristina; Heck, Ailime Perito Feiber (ABCS Health Sciences, 2017)
Introduction: The Hospital Cancer Registry (HCR) is a systematic source of information aimed to improve the service provided to all cancer patients. Its database is essential for all professionals who attend to patients with cancer as it provides statistical data that allows to determinate the profile of patients, and so to direct the therapy to be adopted. Objective: To evaluate the completeness of the clinical and surgical oncology medical records of Maternity Carmela Dutra in 2009 and 2010, based on the variables of the HCR. Methods: A descriptive exploratory study was conducted with a secondary database provided by HCR. Cutoff points with different degrees were used for analysis of incompleteness of information from medical records. Results: Of the 405 records analyzed, 8.9% were in the poor category, 22.7% were classified in the fair category, 32.6% in the good and 35.8% in the excellent category. Family history of cancer and alcohol consumption remained largely the missing cases in the medical records. Conclusion: This study highlights the importance and need for improvement of medical records, with the structuring of required fields and standardization of medical records system.